2004
DOI: 10.1074/jbc.m310349200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Collagenase Activities of Human Cathepsins by Glycosaminoglycans

Abstract: Cathepsin K, a lysosomal papain-like cysteine protease, forms collagenolytically highly active complexes with chondroitin sulfate and represents the most potent mammalian collagenase. Here we demonstrate that complex formation with glycosaminoglycans (GAGs) is unique for cathepsin K among human papain-like cysteine proteases and that different GAGs compete for the binding to cathepsin K. GAGs predominantly expressed in bone and cartilage, such as chondroitin and keratan sulfates, enhance the collagenolytic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
212
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(230 citation statements)
references
References 48 publications
13
212
1
4
Order By: Relevance
“…Previous studies have shown that excess GAG accumulation inhibits the degradation of collagen type II by cathepsin K, resulting in impaired osteoclast activity and decreased cartilage resorption. This contributes to the skeletal abnormalities seen in the MPS1 human disease and the mouse model 43, 44. Significant normalization of bone volume and density values in our treated mice is further evidence of the therapeutic reduction of systemic GAGs achieved via liver‐directed hAEC transplantation.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies have shown that excess GAG accumulation inhibits the degradation of collagen type II by cathepsin K, resulting in impaired osteoclast activity and decreased cartilage resorption. This contributes to the skeletal abnormalities seen in the MPS1 human disease and the mouse model 43, 44. Significant normalization of bone volume and density values in our treated mice is further evidence of the therapeutic reduction of systemic GAGs achieved via liver‐directed hAEC transplantation.…”
Section: Discussionsupporting
confidence: 58%
“…Although the human genome encodes .500 proteases, only a small subset of these gene products-confined largely to the MMP and cysteine proteinase families-can degrade intact type I or II collagen molecules within their triple-helical domains (5)(6)(7)(8)(9)(10)(11). RA synoviocytes have been reported to express multiple collagenases (1-3, 12-19), but the dominant effectors capable of supporting either collageninvasive or collagen-destructive phenotypes under pathophysiologically relevant conditions have remained the subject of controversy (3).…”
Section: Discussionmentioning
confidence: 99%
“…Although the cartilaginous matrix is dominated by type II collagen, the extracellular matrix of ligaments, tendons, and bone is largely composed of type I collagen (1)(2)(3). Presently, triple-helical collagenases (i.e., those proteinases that are able to hydrolyze collagen by cleaving within triplehelical domains) are limited to members of the matrix metalloproteinase (MMP) and cysteine proteinase families (5)(6)(7)(8). Within the MMP family, four secreted collagenases have been identified: MMP-1 (the so-called fibroblast collagenase), MMP-8 (collagenase-2), MMP-13 (collagenase-3), and MMP-2 (gelatinase A) (3,5,9).…”
mentioning
confidence: 99%
“…HS and DS both accumulate during the pathology of MPS I disease 1 and have both been shown to inhibit the type I collagenolytic activity of cathepsin K. 11 However, due to the lack of an appropriate antibody for DS, we have only described HS staining. The growth plate of the femur at the shoulder joint, the tibia at the knee joint, and the spine, were stained for cathepsin K and HS, and the overlapping area resulting in orange fluorescence was measured ( Figure 3A).…”
Section: Hs and Cathepsin K Colocalizationmentioning
confidence: 99%
“…10 However other GAGs, like DS and HS, were shown to inhibit the collagenolytic activity of cathepsin K. 11 As both DS and HS are present in high concentrations in MPS I tissue, we investigated the effect these concentrations would have on cathepsin K activity. During endochondral ossification, cathepsin K degrades type II collagen (cartilage) below the growth plate area to provide room for new bone to be laid down by osteoblasts.…”
mentioning
confidence: 99%